2020
DOI: 10.1021/acssuschemeng.9b06450
|View full text |Cite
|
Sign up to set email alerts
|

Material Characterization-Based Wear Mechanism Investigation for Biomass Hammer Mills

Abstract: Biomass, as harvested, is composed of inorganic compounds both intrinsically and extrinsically and can be abrasive. The present study investigates the wear modes and mechanisms of two types of blades of hammer mills used in biomass size reduction (impacting the particle size and distribution) and densification (impacting the size, shape, and density). The dominant wear modes for the stage 1 steel blades are determined to be erosive and polishing wear. For the stage 2 blades with a carbide weld overlay, the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Task 1 currently focuses on issues related to wear and durability of components used in unit operations to pretreat feedstocks arriving from the field/forest to the entrance of biochemical or thermal reactors where the feedstocks are converted into useful products. Studies [6,7] have shown that mechanical wear can be significant, with wear clearly visible to the naked eye. The wear can add significant delays in processing feedstocks due to high downtimes to replace worn components, but also to clear jams that occur in milling units.…”
Section: Figure 1 Illustration Of Physical Form Of Corn Stover Feedstmentioning
confidence: 99%
“…Task 1 currently focuses on issues related to wear and durability of components used in unit operations to pretreat feedstocks arriving from the field/forest to the entrance of biochemical or thermal reactors where the feedstocks are converted into useful products. Studies [6,7] have shown that mechanical wear can be significant, with wear clearly visible to the naked eye. The wear can add significant delays in processing feedstocks due to high downtimes to replace worn components, but also to clear jams that occur in milling units.…”
Section: Figure 1 Illustration Of Physical Form Of Corn Stover Feedstmentioning
confidence: 99%
“…Size reduction is an essential step in the biomass-fuel conversion process . First, this step helps increase the bulk density of the feedstock through a smaller particle size, thereby reducing the cost of handling, storage, and transportation. Since the feedstock surface area is increased, the conversion rate and yield are also enhanced. Size reduction often is achieved by mechanical milling machines, such as hammer mill, knife mill, ball mill, drum/disc mill, and so on. In particular, hammer mills have been widely used because they are relatively inexpensive, easy to operate and maintain, feasible for various biomass materials, and capable of producing feedstocks of different sizes. , However, hammer mills consume more energy than desired, and the energy consumption is exponentially increased as the screen size decreases . Furthermore, hammer mills experience difficulties in grinding of high-moisture biomass feedstocks (above around 20 wt %) because of their high toughness. , Hammer mills, because of the crushing mode, also produce a significant amount of fines that are not usable in common conversion processes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, severely worn hammers were reported to reduce the productivity of the hammer mill up to 55%, worn dull blades of drum chipper were observed to increase the time for processing a unit mass of feedstock by 30% with 39% more fuel consumption, and worn knives on a disc chipper caused a 50% lower productivity and 1.4 to 2.8 times higher specific fuel consumption in processing chestnut and locust fuel wood . Biomass inorganic content (often called “ash”) has been found to be largely responsible for the processing tool wear. , There is intrinsic inorganic content inside the plant cells and tissues as a result of normal physiological processes and extrinsic inorganic particles (EIPs), typically soil or dust contamination either adhered to the biomass surface or collected during harvest. The abrasiveness of the biomass feedstock depends on the concentration, chemical composition, and particle size and shape of the inorganic compounds. EIPs were reported with high hardness of 6.5–7.5 Mohs. , Detailed characterizations of the inorganic compounds of corn stover and pine residue have been conducted recently .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations